2015
DOI: 10.1055/s-0035-1547264
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Palm Cooling’s Impact on Resistive Exercise Performance

Abstract: To examine palm cooling's (15 °C) impact, subjects performed 3 four-set leg press workouts in a randomized sequence. Per workout they received 1 of 3 treatments: no palm cooling, palm cooling between sets, or palm cooling between sets and post-exercise. Dependent variables were examined with three-way ANOVAs; average power underwent a three-way ANCOVA with body fat percentage as the covariate. Simple effects analysis was our post hoc and α=0.05. Left hand skin temperatures produced a two-way interaction (no pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 27 publications
1
17
0
1
Order By: Relevance
“…Intermittent palm cooling between 4 subsets of leg press resistance exercise resulted in a delayed decrement of average power output, resulting in a higher power output in the fourth subset of leg press exercise 62,63 . A potential explanation for this finding may relate to temporarily overriding sensations of fatigue 62 . The peripheral thermal input may result in a lower awareness of effort while using palm cooling.…”
Section: Per-coolingmentioning
confidence: 99%
“…Intermittent palm cooling between 4 subsets of leg press resistance exercise resulted in a delayed decrement of average power output, resulting in a higher power output in the fourth subset of leg press exercise 62,63 . A potential explanation for this finding may relate to temporarily overriding sensations of fatigue 62 . The peripheral thermal input may result in a lower awareness of effort while using palm cooling.…”
Section: Per-coolingmentioning
confidence: 99%
“…Peripheral cooling strategies have recently attracted attention given their promising effects on neuromuscular activation [ 7 , 8 , 9 ] and resistance-based exercise performance [ 10 , 11 , 12 , 13 , 14 ]. That is, cooling the joints near exercising muscles, [ 7 , 8 , 9 ] or the extremities (e.g., palms [ 10 , 11 , 12 , 13 ] or feet [ 14 ]) far from exercising muscles rather than cooling the muscle itself may attenuate performance because of reduced muscle temperature below the optimal range [ 15 , 16 ]. Cooling the ankle increases motor neuron excitability as assessed by artificial electrical stimulation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cooling the ankle increases motor neuron excitability as assessed by artificial electrical stimulation [ 7 ]. Resistance exercise studies demonstrated that palm cooling between a four-set, eight-repetition concentric flywheel leg press at a submaximal level of effort hastens blood lactate clearance and delays average power decrements [ 11 ]. In addition, during four sets of 85% one-repetition maximum (1 RM) bench press to exhaustion workout, inter-set palm cooling at 10 °C for 2.5 min increases the repetitions, total exercise volume, and root mean square (RMS) electromyography (EMG) of some exercising muscles for resistance-trained male and female participants [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, using an intermittent palm cooling device during a repeated leg press resistance exercise resulted in a higher power output [145,146]. It has been hypothesized that palm cooling allows a lower level of inhibition in the number of activated motor units, which results in a higher power output and number of repetitions [146].…”
Section: Per-cooling and 'Anaerobic' Performancementioning
confidence: 99%